2008
DOI: 10.1007/s10067-008-0877-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and medical management of patients with rheumatoid arthritis and ankylosing spondylitis

Abstract: Rheumatoid arthritis (RA) and ankylosing spondylitis (AS) are chronic, progressive, systemic inflammatory rheumatic diseases that lead to serious disability. The objective of this study was to investigate the demographic and clinical characteristics of the patients with RA and AS who were treated in tertiary hospitals in Turkey and to analyze their current medical management. A total of 562 RA and 216 AS patients were evaluated. The mean age of RA patients was 52.1 +/- 12.6 years. The female to male ratio was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
3
5

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 20 publications
5
31
3
5
Order By: Relevance
“…Previous studies have reported significantly higher BASFI scores in patients with AS who have high disease activity compared with those exhibiting low disease activity, and [25,26] our findings were consistent with these results. The BASFI score was higher in the group with BASDAI scores of ≥4, and it was significantly correlated with the BASFI.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported significantly higher BASFI scores in patients with AS who have high disease activity compared with those exhibiting low disease activity, and [25,26] our findings were consistent with these results. The BASFI score was higher in the group with BASDAI scores of ≥4, and it was significantly correlated with the BASFI.…”
Section: Discussionsupporting
confidence: 92%
“…This ratio is in keeping with previous studies. [9,10] Sany et al [10] in their study with French RA patients found the average age of disease onset to be 44 years old, and our study had a similar age of 42.…”
Section: Discussionsupporting
confidence: 72%
“…[16] Rheumatoid factor was found to be positive in 60-80% of RA patients. [17] In the aforementioned study by Calgüneri et al, [14] 68.3% of patients were found to be RF positive, whereas RF positivity was 72.2% in the multi-centered study of Bodur et al [9] In our study, RF positivity was 59.4%, which is lower than in previous studies. The lower rate of RF positivity most probably comes from the calibration difference between laboratories.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations